Poeci - to są słów malarze... : typy relacji między słowem a obrazem w książkach poetyckich okresu Młodej Polski - Bajda, Justyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The present book examines the relations between the word and the image in the poetry ofthe Young Poland period. The issues analysed by the author fall within the fi eld of comparativecultural studies. The objective is to determine the types of intersemiotic situations inwhich the poetic word and image could fi nd themselves in poetic works from the YoungPoland period.The division which is the basis of the word-image relations discussed here – proposedby the French semiotician Bernard Vouilloux – can be described as based on two maintypes of relations: in praesentia and in absentia. This distinction was subject to a simultaneouspresence of linguistic and iconic signs or a lack of either of these elements within a sheetof paper or canvas.The in praesentia relations comprise four types of associations. The fi rst occurs when theword is clearly subordinated to the image. The text is inscribed in the image; it becomesa linguistic semantic enclave within iconic signs. The reverse takes place when the image issubordinated to the text, usually serving as its ornamentation. Another subgroup includesfi gures combining linguistic and iconic elements, which can complement each other but alsomerge (a letter becomes an image, an image – a letter). The last group comprises imagesthat accompany the written word as illustrations. Within the poetic works from the YoungPoland period, the author analyses the following relations: 1. initials; 2. ornamental decorationsand illustrations; 3. visual poetry; 4. linguistic semantic enclaves within illustrations.
Keywords: poezja polska -- 1870-1914 -- historia i krytyka; sztuka i literatura -- Polska -- 1870-1914; sztuka książki -- 1870-1914; ekfrazy (retoryka)